Electrowetting actuation of a dye-doped fluorescent droplet - Mero, Rea Divina C (Archīum Ateneo, 2014)
We report tunable color output from a fluorescent dye-doped droplet actuated by electrowetting. The system design, based on a planar electrowetting set-up, is compact and straightforward, with minimal voltage requirements for effective actuation. Fluorescent droplets are sourced from a 1 mM solution of rhodamine 6G in distilled water. Initial contact angle for a dye-doped droplet is 72.1o.At a maximum applied voltage of 20 V, the contact angle decreases to 56.5o . Emission spectra are collected as the droplet fluoresces under UV illumination. Over an electrowetting voltage range of 0 to 20 V, the peak fluorescence wavelength shifts from 568 to 546 nm.